Linux all-in-one for dummies - Dulaney, Emmett (--For dummies., 2014)
Eight minibooks in one volume cover every important aspect of Linux and everything you need to know to pass level-1 certification Linux All-in-One For Dummies explains everything you need to get up and running with the popular Linux operating system. Written in the friendly and accessible For Dummies style, the book ideal for new and intermediate Linux users, as well as anyone studying for level-1 Linux certification. The eight minibooks inside cover the basics of Linux, interacting with it, networking issues, Internet services, administration, security, scripting, and level-1.